An Improved CRISPR/Cas9 System for Genome Editing in Populus by Using Mannopine Synthase (MAS) Promoter - An, Yi; Geng, Ya; Yao, Junguang; Wang, Chun; Du, Juan (Frontiers in Plant Science, 2021)
Gene editing technology in woody plants has great potential for understanding gene function, and altering traits affecting economically and ecologically important traits. Gene editing applications in woody species require a high genome editing efficiency due to the difficulty during transformation and complexities resulting from gene redundancy. In this study, we used poplar 84K (Populus alba × P. glandulosa), which is a model hybrid for studying wood formation and growth. We developed a new CRISPR/Cas9 system to edit multiple genes simultaneously. Using this system, we successfully knocked out multiple targets of the PHYTOENE DESATURASE 8 in poplar. We found the mutation rate of our CRISPR/Cas9 system is higher (67.5%) than existing reports in woody trees. We further improved the mutation rate up to 75% at editing sites through the usage of the mannopine synthase (MAS) promoter to drive Cas9. The MAS-CRISPR/Cas9 is an improved genome-editing tool for woody plants with a higher efficiency and a higher mutation rate than currently available technologies.